Effects of limit feeding cold stressed growing calves in the morning versus the evening, as well as bunk line sharing on performance - Sasscer, Charles A., III (Kansas State University, 2021)
Two growth performance studies and two digestibility trials were conducted to evaluate limit feeding cold stressed growing calves in the morning versus the evening, as well as bunk line sharing and a study to evaluate the effects of limit feeding corn grain containing an alpha-amylase gene to growing cattle. In the first trial, there was one diet offered at 2.0% of body weight on a DM basis. Diets were formulated to provide 1.32 Mcal NEg/kg DM. The experiment consisted of one treatment fed in the morning (AM), one in the evening (PM), one fed half of their feed in the morning and half in the evening (AM/PM), and two additional groups of cattle (Shuttle AM, Shuttle PM) that were fed in the same pen yet were rotated twice daily utilizing an adjacent holding pen. ADG for calves fed in the evening and/or assigned to share a bunk line was not significantly different (P>0.9) compared to calves fed in the morning and not rotated daily. Feed efficiency was not improved in calves fed in the evening nor shuffled between pens (P>0.98). A digestibility trial was conducted concurrently to the first trial using 6 cannulated Holstein steers receiving the same treatments, less the bunkline sharing. Ruminal pH did not differ between treatments (P > 0.35), and ruminal VFA concentrations of propionate and valerate were higher for PM fed calves while concentrations of isobutyrate and isovalerate were lower for PM fed calves (P<0.03). Altering time of feed delivery during times of cold stress and cattle housing management changes digestibility characteristics of the rumen but does not result in any cattle growth performance advantages. In the second experiment, there were a total of four diets offered at 2.2% of body weight on a dry matter (DM) basis. The four diets consisted of two varieties of corn (Enogen Feed Corn (EFC) vs. negative isoline control corn (CON)) with two different methods of corn processing (dry-rolled corn (DRC) vs. whole-shelled corn (WC)) and were formulated to provide 1.32 Mcal NEg/kg DM. ADG and final BW were not significantly different for calves fed EFC (P > 0.56). Feed efficiency was not different for calves fed EFC (P > 0.94), or for calves fed DRC (P>0.26). A digestibility trial was conducted concurrently using 8 cannulated beef steers fed the same 4 diets as the second experiment. Ruminal pH was not affected by corn hybrid (P > 0.34). EFC fed cattle produced greater concentrations of ammonia and isovalerate (P<.02), as well as having greater digestion of ADF and NDF (P<0.03). Feeding corn grain containing an alpha-amylase gene alters digestion characteristics of the rumen but does not result in improved cattle performance.
Keywords: Enogen Feed corn; Growing cattle; Evening feeding; Bunkline sharing